THE USE OF DIGITAL FEEDBACK ON ELSA SPEAK IN LEARNING PRONUNCITAION FOR SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Enni Erawati Suragih; Nur’aini Putri Tabrani; Nur Muthmainnah (STKIP PGRI Jombang, 2021)
In learning English, students must be equipped with knowledge of good and correct pronunciation so that they can be a support for students in English pronunciation. One application that can be used to practice pronunciation by Artificial Intelligence is ELSA Speak. In ELSA Speak, students can learn the correct pronunciation generated from native speakers, and can practice their pronunciation and get digital feedback from ELSA Speak, and correct their pronunciation. Two main discussions were the implementation of digital feedback on Elsa Speak for students and the benefits of digital feedback on ELSA Speak in learning English. This research uses qualitative case studies, in which observation and semi-structured interviews were used as instruments in collecting the data. The result of the research shown that ELSA Speak can help students to learn how to pronounce some words, and this application can make the students be more confident when want to talk with English language.